A new composite hydrogel combining the biological properties of collagen with the mechanical properties of a supramolecular scaffold for bone tissue engineering. (10th December 2017) - Maisani, Mathieu; Ziane, Sophia; Ehret, Camille; Levesque, Lucie; Siadous, Robin; Le Meins, Jean‐François; Chevallier, Pascale; Barthélémy, Philippe; De Oliveira, Hugo; Amédée, Joëlle; Mantovani, Diego; Chassande, Olivier
Abstract: Tissue engineering is a promising alternative to autografts, allografts, or biomaterials to address the treatment of severe and large bone lesions. Classically, tissue engineering products associate a scaffold and cells and are implanted or injected into the lesion. These cells must be embedded in an appropriate biocompatible scaffold, which offers a favourable environment for their survival and differentiation. Here, we designed a composite hydrogel composed of collagen I, an extracellular matrix protein widely used in several therapeutic applications, which we associated with a physical hydrogel generated from a synthetic small amphiphilic molecule. This composite showed improved mechanical and biological characteristics as compared with gels obtained from each separate compound. Incorporation of the physical hydrogel prevented shrinkage of collagen and cell diffusion out of the gel and yielded a gel with a higher elastic modulus than those of gels obtained with each component alone. The composite hydrogel allowed cell adhesion and proliferation in vitro and long‐term cell survival in vivo. Moreover, it promoted the differentiation of human adipose‐derived stem cells in the absence of any osteogenic factors. In vivo, cells embedded in the composite gel and injected subcutaneously in immunodeficient mice produced lamellar osteoid tissue and differentiated into osteoblasts. This study points this new composite hydrogel as a promising scaffold for bone tissue engineering applications.